Move to intelligence-driven security. (August 2015) - Knights, Ricky; Morris, Emma
Abstract : Today's disruptive enterprises are primed for unprecedented security challenges. The evidence is already compelling: cyber-attacks and network breach incidents are increasing in frequency, volume and complexity, reaching an alarmingly high level, drilling holes in the networks of the world's top business corporations (Fortune 500 firms included) and government establishments. For CSOs and CISOs, the question to ask is, what has happened to next-generation firewalls and endpoint protection?